Phytochemicals Analysis, In Vitro Antibacterial Activities of Extracts, and Molecular Docking Studies of the Isolated Compounds from Melhania zavattarii Cufod Leaves - Teshome Gonfa; Ayalew Temesgen; Olyad Erba; Ephriem T. Mengesha; Muthusaravanan Sivasubramanian (Journal of Tropical Medicine)
Melhania zavattarii Cufod is an endemic plant species to Ethiopia and is used to treat ailments related to kidney infection. The phytochemical composition and biological activity of M. zavattarii have been not reported yet. Therefore, the present work aimed to investigate phytochemical constituents and evaluate the antibacterial activity of different solvents’ leaf extracts and analyze the molecular binding capacity of isolated compounds from the chloroform leaf extract of M. zavattarii. Accordingly, preliminary phytochemical screening was tested by using standard procedures and the result indicated that phytosterols and terpenoids as major and others like alkaloids, saponins, flavonoids, tannins, phlobatannin, and coumarins were detected as minor in extracts. Antibacterial activity of the extracts was evaluated using the disk diffusion agar method, and the activities revealed that chloroform extract showed the highest inhibition zones, 12.08 ± 0.38, 14.00 ± 0.50, and 15.58 ± 0.63 mm against Escherichia coli at 50, 75, and 125 mg/mL concentrations, respectively, compared to that of n-hexane and methanol extracts at respective concentrations. Methanol extract showed the highest zone of inhibition 16.42 + 0.52 against Staphylococcus aureus at 125 mg/mL concentration compared to that of n-hexane and chloroform extracts. Two compounds, namely, β-amyrin palmitate (1) and lutein (2) were isolated and identified for the first time from the chloroform leaf extract of M. zavattarii, and structural elucidations of these compounds were accomplished by using spectroscopic methods (IR, UV, and NMR). For the molecular docking study, 1G2A, which is a protein of E. coli and chloramphenicol standard target, was selected. Binding energies of −9.09, −7.05, and −6.87 kcal/mol were calculated for β-amyrin palmitate, lutein, and chloramphenicol, respectively. The drug-likeness property result indicated that both β-amyrin palmitate and lutein violated two rules of Lipinski’s rule of five with molecular weight (g/mol) > 500 and LogP > 4.15. In the near future, further phytochemical investigation and biological activity evaluation should be conducted on this plant.